A non-healing chronic plaque on buttocks in a child: Lupus vulgaris - Zawar, Vijay; Chuh, Antonio; Gugle, Anil; Sankalecha, Sudhir (Journal of Pediatric Infectious Diseases, 2007)
Cutaneous tuberculosis is a major cause of morbidity in children in India. Lupus vulgaris is one of the commonest manifestations. The clinical recognition of lupus vulgaris may be difficult with atypical presentation. It is important to have a high index of suspicion to recognize and treat these children to prevent morbidities. The buttocks are common but often neglected sites for lupus vulgaris in children. We present a case report of lupus vulgaris occurring on the buttocks, and discuss our approach in diagnosis and treatment.
Keywords: Cutaneous tuberculosis; diascopy; scrofuloderma; tuberculosis